ANALISIS PENGARUH KUALITAS PELAYANAN, HARGA, CITRA MEREK DAN WORD OF MOUTH TERHADAP KEPUASAN PELANGGAN TRANSPORTASI ONLINE (GOJEK) - Harun Raudhatul Na’im; Wiyadi (POLITEKNIK LP3I JAKARTA, 2024)
This study aims to analyze the effect of service quality, price, brand image and word of mouth on online transportation customer satisfaction (gojek). This research method is quantitative. In this study, the population used is all people who have used Gojek Transportation services. The sampling technique in this study used purposive sampling. The data used in this study are primary data. The data collection method used in this study was a questionnaire. The data analysis technique used in this research is Multiple Linear Regression using the SPSS 25 test tool with validity test, reliability test, classical assumption test, hypothesis testing, f test, and t test, and determination coefficient test. The results showed that service quality has a positive and significant effect on customer satisfaction. Price has no significant effect on customer satisfaction. Brand image has a positive and significant effect on customer satisfaction. Word of mouth has a positive and significant effect on customer satisfaction.